To study export performance Rras Bakti (M) Sdn Bhd to Indonesia market / Nuraini Mohd Amin - Mohd Amin, Nuraini (Faculty of Business and Management, 2010)
Basically, the company faced demand uncertainty and new retailing practices, by using conventional outsource. Hence, it will become their traditional rate of doing business. Mostly, this situation will reflect to the decline economic condition. By using an intermediaries or channel of distribution, it becomes one of major cost to them. The company thinks that either to continue with the intermediaries or just eliminate it. The point of this case study is to see whether the intermediaries as a channel of distribution or agree to their own distribution channel and they also can be describe as an outsource provider. However, they are known as an agent to supply the product to their client. In this case study, the main point is to look on how the achievement, performance and effort of intermediaries as an agent can boost up the sale product of Rras Bakti (M) Sdn Bhd.